UMETNOST: NJENA RELATIVNOST, VREDNOST IN PARTIKULARNOST (Филолошки студии, 2019)
The article deals above all with the question of the value of a work of art. It concludes that the value is relative to the effects the work of art produces. These effects are context dependent, therefore the value of a work of art is also context relative. There are no available rules for artistic effects and judgement, therefore in art prediction is not possible. What is possible is the explanation of artistic effects in retrospect. The author organises the reflection on the inherent, specific value of art around two axes: the metaphysical axis and the axis of a new (artistic) experience which makes self-knowledge possible.